1695 Which clinical features best predict occult scaphoid fracture? A systematic review and meta-analysis. Issue 12 (22nd November 2022) - Coventry, Laura; Oldrini, Ilaria; Novak, Alex; Dean, Ben; Metcalfe, David
Abstract : Aims, Objectives and Background: Scaphoid fractures require early identification to avoid complications such as painful non-union, avascular necrosis, and chronic wrist pain. Unfortunately, plain radiographs are insufficiently sensitive and so patients may require immobilisation and further imaging (e.g. MRI) despite normal initial radiographs. The aim of this systematic review was to determine which clinical features best predict the presence of an occult scaphoid fracture that warrants immobilisation and further imaging. Method and Design: A systematic review of diagnostic test accuracy studies was undertaken. All study designs were included if they evaluated predictors of scaphoid fracture amongst patients with normal initial scaphoid radiographs. Quality assessment was undertaken using the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool. Depending on the number of studies, data were presented as individual data points, ranges, or meta-analysed by fitting either univariate random effects or multi-level mixed effects logistic regression models. Results and Conclusion: Eight studies reported data on 1, 685 wrist injuries. The prevalence of scaphoid fracture despite normal radiographs was 7.3%. The most accurate predictors of occult scaphoid fracture were pain with supination against resistance (sensitivity 100%, specificity 97.9%, LR 45.0 [95% CI 6.5–312.5], supination strength <10% of contralateral side (sensitivity 84.6%, specificity 76.9%, LR 3.7 [95% CI 2.2–6.1]), pain on ulnar deviation (sensitivity 55.2%, specificity 76.4%, LR 2.3 [95% CI 1.8–3.0]), and pronation strength <10% of contralateral side (sensitivity 69.2%, specificity 64.6%, LR 2.0 [95% CI 1.2–3.2]). The absence of anatomical snuffbox tenderness significantly reduced the likelihood of an occult scaphoid fracture (sensitivity 92.1, specificity 48.4, LR- 0.2 [95% CI 0.4–0.7]). In conclusion, no single feature can satisfactorily exclude occult scaphoid fracture. However, a number of clinical findings significantly affect the pre-test likelihood of fracture. Future work should determine whether combinations of clinical findings can be used to guide which patients require immobilisation and further imaging despite normal initial radiographs.